Kualitas Guru dalam Meningkatkan Mutu Pendidikan di Indonesia - Ida Rohmah Susiani; Nur Diny Abadiah (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2021)
Metrics to determine the goodness of a nation’s education level and how it fares when compared to other nations are continuously developed and updated. It is important because the growth of various aspects in a nation, whether directly or indirectly, is tied to the quality of education for the people. In a list of 14 developing countries, Indonesia ranked 10th in academic quality and 14th in teacher quality. This highlights a national urgency to focus and improve on our teachers’ quality for the nation’s overall education standard to rise. The aims of this research are to apply the literature study method to investigate previous studies on the topic of education practitioners and identify the possible solutions to improve them. The identified solutions are largely classified into 3 according to the party largely responsible to practice it, namely: i) the teachers, ii) the academic institutions, and iii) the government. These solutions are not isolated from one another; all three are needed to function together to achieve a synchronized improvement on teachers quality, and in turn, overall education quality in Indonesia.